Advanced Security Measures for Virtualized Data Storage: A Comprehensive Study - Yan Zhang (Innovation in Science and Technology, 2025)
With the widespread application of virtualization technology in data centers, the security issues of data storage have become increasingly prominent. This paper aims to explore the application of information security in virtualized data storage to address the increasingly complex security challenges. The article first reviews the development of virtualization technology and the key technologies of virtualized data storage, then analyzes the current state and threats faced by information security in virtualized environments. Based on this, the paper discusses security requirements such as data integrity, access control, and privacy protection in detail, and delves into the application of information security technologies such as data encryption, intrusion detection and defense systems, security information and event management, and virtualization security policy management. Furthermore, this paper proposes a comprehensive security framework for virtualized data storage and describes its design principles, component architecture, and implementation deployment strategies in detail. Through experimental design and case studies, the paper validates the effectiveness of the proposed framework and evaluates its performance. Finally, the paper summarizes the research findings and proposes prospects for future research directions. This study not only provides theoretical support and practical guidance for information security in virtualized data storage but also offers valuable references for researchers and practitioners in related fields.